The Influence Of Perceived Ease Of Use And Perceived Usefulness Through Satisfaction On User Loyalty To The Sipp Online Application Of Bpjs Employment Banyuwangi Branch Office: English - Hanif Bagus Azhar; Yuniorita Indah Handayani; Lia Rachmawati (Journal of Management, 2025)
Abstract This study aims to analyze the influence of Perceived Ease of Use and Perceived Usefulness on User Satisfaction and User Loyalty of the SIPP Online Application at BPJS Ketenagakerjaan Banyuwangi Branch, as well as the mediating role of User Satisfaction. This research employs a quantitative approach using survey methods conducted on users of the application. Data analysis was carried out through regression testing and mediation analysis. The results show that Perceived Ease of Use has a positive and significant effect on User Satisfaction and User Loyalty. Similarly, Perceived Usefulness positively influences Satisfaction and Loyalty. Furthermore, User Satisfaction has a direct and significant impact on User Loyalty. The mediation test reveals that User Satisfaction mediates the effect of Perceived Ease of Use and Perceived Usefulness on Loyalty, indicating that the ease of use and perceived benefits of the application indirectly enhance loyalty through increased satisfaction.These findings strengthen the Technology Acceptance Model (TAM) theory and highlight the importance of satisfaction as a mediating variable between user perceptions and long-term loyalty. The practical implication of this research is the need for continuous development of user-friendly interfaces and functional features to foster user loyalty. This study also contributes theoretically to the understanding of user behavior in public service digital applications in Indonesia